(3QSGdI GdeYQGLs - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s
(3ChdgG (B:s
(3bGd ehdGfG eMeO Hf YeQ GdQGRi JZeOg Gddg HZaQGfg HGH ai GdeYQGL hajg GdaUd GdChd ai HjGf EecGfg EYde Cf GdeYQGL dg ef JHJGf eYQGL ef ecI Edi HjJ GdebOS heYQGL ef HjJ GdebOS Edi GdSehGJ s
(3BNQgG (B:s
(3hGdLRA jfLPH Zdi Gdcd hYGde GdSehGJ YGde GdGQhGM GdWGgQI GdebOSI adgPG GdSHH MUd Pdc GdESQGA hGddg CYde HGdUhGH hZdjg GdeQLY hGdeCH s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3GdLeYjI GdGSjhjI (B_ (3cdcJG (B(636(1)) s
Keywords: (3GdJhMjO hGdedd hGdfMds